2014
DOI: 10.1007/s00449-014-1327-x
|View full text |Cite
|
Sign up to set email alerts
|

Filamentous bacteria existence in aerobic granular reactors

Abstract: Filamentous bacteria are associated to biomass settling problems in wastewater treatment plants. In systems based on aerobic granular biomass they have been proposed to contribute to the initial biomass aggregation process. However their development on mature aerobic granular systems has not been sufficiently studied. In the present research work filamentous bacteria were studied for the first time after long term operation (up to 300 days) of aerobic granular systems. Chloroflexi and Sphaerotilus natans have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 36 publications
2
9
1
2
Order By: Relevance
“…A fast decrease of the abundance of filamentous‐shape organisms occurred when the settling time of the SBR operational cycle was shortened and they were washed‐out. Even though in previous studies filamentous bacteria showed a structural function in the stability of aerobic granules, microbial results of the present study suggested that heterotrophic bacteria acquired the role of binding material, as it will be discussed in the following section.…”
Section: Resultscontrasting
confidence: 51%
“…A fast decrease of the abundance of filamentous‐shape organisms occurred when the settling time of the SBR operational cycle was shortened and they were washed‐out. Even though in previous studies filamentous bacteria showed a structural function in the stability of aerobic granules, microbial results of the present study suggested that heterotrophic bacteria acquired the role of binding material, as it will be discussed in the following section.…”
Section: Resultscontrasting
confidence: 51%
“…These four genera have earlier been reported in different granular sludge reactors operated for organic carbon and nitrogen removal (Li et al, 2008; Ebrahimi et al, 2010; Liu et al, 2010; Zhao et al, 2013, 2015; Kong et al, 2014; Lv et al, 2014; Cydzik-Kwiatkowska, 2015; Figueroa et al, 2015). Thauera and Zoogloea have been found at both low and high OLRs, between 1 and 15 kg COD m -3 d -1 (Ebrahimi et al, 2010; Zhao et al, 2013; Lv et al, 2014).…”
Section: Resultsmentioning
confidence: 58%
“…Thauera and Zoogloea have been found at both low and high OLRs, between 1 and 15 kg COD m -3 d -1 (Ebrahimi et al, 2010; Zhao et al, 2013; Lv et al, 2014). Meganema has been found to be abundant in reactors operated at 1.5–3 kg COD m -3 d -1 , treating industrial or synthetic wastewater (Kong et al, 2014; Figueroa et al, 2015). Paracoccus has been reported at loading rates of 1.5–3.3 kg COD m -3 d -1 , in reactors treating synthetic wastewater, and in wastewater polluted with pharmaceuticals (Lv et al, 2014; Cydzik-Kwiatkowska, 2015; Zhao et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies suggested that the presence of X S in the wastewater results in aerobic granules with filamentous outgrowths on their surfaces (Schwarzenbeck et al, 2004(Schwarzenbeck et al, , 2005De Kreuk et al, 2010;Peyong et al, 2012;Figueroa et al, 2015). The development of filamentous and finger-type structures can be explained by the existence of substrate gradients inside the sludge aggregates due to diffusion limitation (Martins et al, 2004;De Kreuk et al, 2010;Weissbrodt et al, 2012).…”
Section: Introductionmentioning
confidence: 96%